7 - Football malgache féminin : un exotisme genré ? Étude de cas d’une association locale: DOI: 10.4314/ad.v31i1.22254 - Héas, Stéphane (Africa Development, 2006)
In Madagascar, adult female football exists at the embryonic stage, while it has only appeared recently in some Western countries, and is practiced by a minor- ity in such countries. Such appearance of female football draws curiosity in an international context dominated by sports and politics, which promotes parity while largely maintaining male domination. Madagascar thus focuses on gender relations and resistance to body and cultural changes between men and women, but also between women.